MEASUREMENT OF APPLICATION OF ISO 27001 OF CUSTOMER CELLULAR CARD CONFIDENTIALITY DATA IN PT. XYZ AREA JAKARTA - Krishna Rahadian; Ahmad Juang Pratama (CommIT (Communication and Information Technology) Journal, 2014)
The purpose of this study was to evaluate the effects of the process of ISO 27001 with respect to the confidentiality of customer cellular card Jakarta and to improve cellular card customer data confidentiality at PT.XYZ from data leakage of the customer data due to the third party involvement, clean-desk policy, and access right. Recommendation regarding the improvement is provided after reviewing the confidentiality of customer data. The survey in this study is conducted by questionnaire. From the evaluation results of the questionnaire, it is concluded that the larger customer data leaks are mainly caused by the external factors.